PSYCHOLOGICAL FEATURES OF FORMATION OF LEADERSHIP ABILITY AND DEVELOPMENT OF CREATIVE QUALITIES IN STUDENTS (Web of Teachers: Inderscience Research, 2024)
This article highlights the importance of using educational technologies in the formation of leadership skills and development of creative qualities, independent thinking, creative research, and development of creative thinking in students.